2013
DOI: 10.1186/1477-3155-11-26
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of nanoparticles with proteins: relation to bio-reactivity of the nanoparticle

Abstract: Interaction of nanoparticles with proteins is the basis of nanoparticle bio-reactivity. This interaction gives rise to the formation of a dynamic nanoparticle-protein corona. The protein corona may influence cellular uptake, inflammation, accumulation, degradation and clearance of the nanoparticles. Furthermore, the nanoparticle surface can induce conformational changes in adsorbed protein molecules which may affect the overall bio-reactivity of the nanoparticle. In depth understanding of such interactions can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
654
3
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 862 publications
(676 citation statements)
references
References 100 publications
(95 reference statements)
12
654
3
7
Order By: Relevance
“…Additionally, the curved (spherical) surface of nanoparticles compared to planar surfaces provide extra flexibility and enhanced surface area to the adsorbed protein molecule. 39 In our study, spherical AgNPs were used, and our results showed a significant increase in the WBC, lymphocyte and granulocyte counts even at extremely low doses (2 mg/kg b.w.). This increase might be due to the spherical nature of the AgNPs inside the mice; this shape provided increased flexibility and an enhanced surface area to the adsorbed NP-PC proteins, resulting in an unwanted immune response even at very low doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the curved (spherical) surface of nanoparticles compared to planar surfaces provide extra flexibility and enhanced surface area to the adsorbed protein molecule. 39 In our study, spherical AgNPs were used, and our results showed a significant increase in the WBC, lymphocyte and granulocyte counts even at extremely low doses (2 mg/kg b.w.). This increase might be due to the spherical nature of the AgNPs inside the mice; this shape provided increased flexibility and an enhanced surface area to the adsorbed NP-PC proteins, resulting in an unwanted immune response even at very low doses.…”
Section: Discussionmentioning
confidence: 99%
“…37 This NP-PC formation is aided by several forces, such as hydrogen bonds, solvation forces, van der Waals interaction, and others. 38,39 Nanoparticles can also modify the structure and therefore, the function of the adsorbed proteins in NP-PCs, which thus alter the overall activity of the nanoparticles. This modification of the adsorbed proteins in NP-PCs may involve specific foldings, which may lead to a change in the conformation of the epitopes of the adsorbed protein.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to conformational change in the protein [43]. Thus, the interaction of the nanoparticles with enzymes may be indirect and occurs via nanoparticle-protein corona and not at the bare nanoparticle surface [42]. As nature, size, shape, charge and hydrophobicity of proteins vary depending on plant species and their metabolites, the interactive effect of metabolites with nanoparticles would also be different.…”
Section: Interplay Of Concentration and Timementioning
confidence: 99%
“…An important factor in understanding the mechanism of nanoparticles-induced changes in nitrogenase is to take into account their interaction with proteins. The dispersion of nanoparticles in a biological milieu results in their surface being immediately enveloped by a complex layer of protein known as ''protein corona'' [41,42]. This adsorption of a protein on the surface of nanoparticles strongly depends on its nature, surface chemistry and physicochemical properties.…”
Section: Interplay Of Concentration and Timementioning
confidence: 99%
“…The recent review by Saptarshi et al [140] provides a table summarising the approaches that have been utilised in the recent literature to study nanoparticle-protein interactions, with a focus on methods to assess nanoparticle surface driven protein conformational changes and uptake of nanoparticles by cellular structures. An earlier review included a more diverse set of approaches, including ones routinely used for assessment of protein-protein interactions, including NMR, phage display libraries, limited proteolysis and many others [141].…”
Section: Towards Predicting Nanoparticle Fate and Behavior In Livingmentioning
confidence: 99%